Pengaruh Edukasi Pembrantasan Sarang Nyamuk Terhadap Pengetahuan dan Sikap Pencegahan DBD oleh Siswa SMP di Lampung - David Nakka Gasong; Ribka Septianingsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus infection which is still a public health problem in Indonesia, including in the Seputih Raman area, Central Lampung. The disease can affect all age groups, but most are under 15 years of age. Based on a preliminary study, I observed that DHF was caused by the lack of public support for the prevention of DHF. The lack of cadre personnel who play an active role in preventing DHF, as well as the role of puskesmas health workers in providing public health education about the dangers of DHF cause a lack of attention to this infectious disease. This study aims to determine the effect of education in improving the behavior of Seputih Raman Christian Middle School students for the prevention of dengue. The method used is experimental with pre-test and post-test designs. The sampling technique in this research is total sampling. Data analysis technique using t-test was conducted to analyze the influence of independent and dependent variables. data collection using a questionnaire, namely written questions in the form of a checklist to determine the disease of dengue and how to eradicate mosquito nests. Based on the results of the research and discussion, it can be concluded that the results show that there is an effect of education about PSN on improving behavior after being given PSN education on DHF prevention behavior by Seputih Raman Christian Junior High School students. The results of the respondent's knowledge variable seem to have increased with a pre-test with a value of 3.998 and a post-test with a value of 8.852. The results of the study of the attitude variable the pre-test value of 2.232 is smaller than the post-test value of 6.576. From the research that has been done, the researcher hopes that students will continue to carry out wamatic activities, in order to reduce mosquito larvae in the school environment.